Química forense: métodos analíticos coadyuvante de la administración de la justicia ecuatoriana - Vargas Sinche, Bryan Guillermo (Editorial: Editorial UTMACH, 2023)
Forensic chemistry is a science that allows expanding the possibilities of action of the pharmaceutical biochemist in the judicial field, through the analysis of biological and non-biological substances in the tax investigation. Objective: Identification of analytical methods that the forensic chemist performs for the contribution of Ecuadorian justice. Methodology: Analysis of the regulations in force in 2022, such as the COIP and the Constitution of the Republic of Ecuador, interview with the forensic chemical expert accredited by the Council of the Judiciary of the SNMLCF center, Machala headquarters, and collection of information in the Council of the Judiciary of the City of Machala- Ecuador and scientific literature on the subject under study. Results: In Ecuador, forensic centers located in Pichincha, Guayas, El Oro, Loja, Sucumbíos, Santo Domingo, Manabí, Esmeraldas, Azuay, Tungurahua and Los Ríos have been implemented, in which chemical experts investigate crimes such as: kidnappings, deaths, poisoning, trafficking and drug abuse, also has the ability to practice in specialties such as hematology, chemistry, biology, toxicology. Conclusion: The forensic chemical expert must have the accreditation code granted by the Council of the Judiciary, in accordance with the provisions of art. 511 of the COIP, those who comply may be summoned to carry out expert reports and apply analytical methods of orientation and certainty, among which we can highlight chromatographic techniques, spectrometry, colorimetry, luminol, among others, in the analysis of biological and non-biological samples clarifying the truth of the facts and comply as coadjuvants of the Ecuadorian administration of justice.
La química forense ciencia que permite ampliar las posibilidades de actuación del bioquímico farmacéutico en el ámbito judicial, a través del análisis de sustancias biológicas y no biológicas en la investigación fiscal. Objetivo: Identificación de métodos analíticos que el perito químico forense realiza para la contribución de la justicia ecuatoriana. Metodología: Análisis de las normativas vigentes del 2022 como el COIP y la Constitución de la República de Ecuador, entrevista al perito químico forense acreditado por el Consejo de la Judicatura del centro SNMLCF sede Machala y recolección de información en el Consejo de la Judicatura de la Ciudad de Machala- Ecuador y literatura científica de la temática en estudio. Resultados: En Ecuador se han implementado centros forenses ubicados en Pichincha, Guayas, El Oro, Loja, Sucumbíos, Santo Domingo, Manabí, Esmeraldas, Azuay, Tungurahua y Los Ríos, en el cual los peritos químicos investigan delitos como: secuestros, muertes, intoxicaciones, tráfico y abusos de drogas, además tiene las capacidades de ejercer en especialidades como hematología, química, biología, toxicología. Conclusión: El perito químico forense tiene que contar con el código de acreditación otorgado por el Consejo de la Judicatura, conforme a lo estipulado en el art. 511 del COIP, quienes cumplan podrán ser convocados a realizar los peritajes y aplicar métodos analíticos de orientación y certeza, entre los que podemos destacar las técnicas cromatográficas, espectrometría, colorimetría, luminol, entre otras, en el análisis de muestras biológicas y no biológicas esclareciendo la verdad de los hechos y cumplir como coadyuvantes de la administración de justicia ecuatoriana.
Keywords: COIP; FORENSE; JUSTICIA; PERITO